2011
DOI: 10.1021/ie200379p
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Lignin from Wastewater Generated by Mechanical Pulping Using Activated Charcoal and Fly Ash: Adsorption Kinetics

Abstract: The possible application of adsorption for the removal of lignin-related material found in wastewater generated by mechanical pulping was investigated. Activated charcoal and fly ash were used as adsorbents in batch experiments. The lignin-related material exhibited properties well-suited for adsorption onto both adsorbents, although the sorption capacity of activated charcoal exceeds that of fly ash. The experimental data were fitted to pseudo-first-and pseudo-second-order rate kinetic expressions, and an att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The adsorbents were added to the lignin solutions in 200 mL sample flasks mounted either on a shaker or in a water bath shaker at 200 rpm to keep the adsorbent suspended. The adsorption time for the equilibrium studies was set to 6 h: kinetic studies showed that there was no significant increase in lignin adsorption onto either of the two adsorbents after this time . All samples were filtered using Whatman GF/A fiberglass filters (Schleicher and Schuell, Maidstone, U.K.) to remove the adsorbent.…”
Section: Methodsmentioning
confidence: 99%
“…The adsorbents were added to the lignin solutions in 200 mL sample flasks mounted either on a shaker or in a water bath shaker at 200 rpm to keep the adsorbent suspended. The adsorption time for the equilibrium studies was set to 6 h: kinetic studies showed that there was no significant increase in lignin adsorption onto either of the two adsorbents after this time . All samples were filtered using Whatman GF/A fiberglass filters (Schleicher and Schuell, Maidstone, U.K.) to remove the adsorbent.…”
Section: Methodsmentioning
confidence: 99%
“…When the H 2 O 2 dosage is excessive, the degradation rate of p-NP would decrease with the increase of the H 2 O 2 dosage. This could be attributed to the reaction of cOH with H 2 O 2 and the reaction of two cOH radicals (see eqn (4) and (5)). Both of the two side reactions inhibit the effective utilization of H 2 O 2 and the rapid oxidation of p-NP.…”
Section: Kinetics Of P-np Degradationmentioning
confidence: 99%
“…(1) (5) cOH + organics / intermediates / inorganics (6) Although the Fenton process can oxidize a wide variety of organics, and is even be able to destroy them to produce carbon dioxide (CO 2 ), water (H 2 O) and inorganic salts (eqn (6)), the recycling of the catalyst (Fe 2+ ) cannot be easily achieved, leading to the generation of sludge containing Fe ions. The treatment of the sludge is expensive in terms of labour, reagents, and time, and is complex in operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated charcoal is commonly used for the color removal in the treatment and purification of water and wastewater, with the laboratory characterization of the adsorption kinetics of chromophores on activated charcoal being necessary to optimize relevant parameters, e.g., dose, retention time for the pilot, or large-scale operation. , That said, conventional manual batch-sampling is challenging to acquire real-time data and makes this process laborious. Accordingly, we used the OSEMC system to characterize the adsorption kinetics of 100-mesh activated charcoal (Sigma, St. Louis, USA) in a real-time fashion, using tartrazine with a λ max at 428 nm (Sigma, St. Louis, USA) as a model target.…”
Section: Methodsmentioning
confidence: 99%